Video documental de las representaciones sociales de la cultura urbana Straight Edge en Quito. - Arroba Alarcón, Daniel Mauricio (2017)
The documentary video entitled "MANTENTE FIRME" was held in the city of Quito - Ecuador, with the purpose of analyzing the social representations that are manifested in the urban culture Straight Edge, so people would be able to understand it is different expressions, and in this way It shows an urban movement in our city The audiovisual product has as main protagonists Juan García "Chester", Dennis De La Cruz "DLC" and Ghandy Guaman "Vegan", active members of this movement, who gave us a broad vision about the world of Straight Edge, its relationship with Music, body expressions, and their way of understanding reality. Being an urban culture that does not consume any kind of legal or illegal drugs, members of this movement suffer different kinds of stigmatization, discrimination, and are usually victims of stereotypes generated by people, who know nothing about Straight Edge, The present investigation, besides showing the social representations and processes of stigmatization suffered by the members of this urban culture, shows an emerging counterculture not only in the country but in the world, the new forms of expressions that emerge as part of globalization of information, affecting urban cultures and resulting in cultural hybrids.